The Role of Public Administration in Managing Social Welfare Programs for Vulnerable Groups in Enrekang Regency - Samad, Muhammad Hisbul Wathan; Ahmad, Riswandi; Rahman, Gafur (Journal Social Civilecial, 2024)
This study explores the role of public administration in managing social welfare programs for vulnerable groups in Enrekang Regency, South Sulawesi. Using a qualitative approach, it examines the implementation processes, administrative strategies, challenges, and effectiveness of these programs in a rural context. The research draws on in-depth interviews with local government officials, program coordinators, community leaders, and beneficiaries to gain comprehensive insights into the complexities of managing social welfare initiatives. Findings reveal that collaborative efforts between local governments, NGOs, and community leaders have been instrumental in addressing logistical challenges and resource limitations. Administrative strategies, such as prioritizing urgent needs and enhancing staff training, have improved service delivery. However, financial constraints and geographical isolation remain significant barriers to achieving program efficiency and effectiveness. The study highlights the importance of transparency in financial management, with annual audits and public updates enhancing trust and accountability. Beneficiaries reported varying levels of success, with some noting improved access to basic services, while others faced challenges due to remoteness and administrative inefficiencies. This research contributes to addressing the gap in the literature on rural social welfare program management by providing insights specific to a non-urban setting. It emphasizes the need for tailored strategies to overcome unique challenges in rural administration and provides policy recommendations to enhance program effectiveness. The findings have broader implications for improving social welfare initiatives in similar rural contexts.